histological outcome after interferon therapy in chronic viral hepatitis - M. Enver DOLAR; Faruk MEMİK; Macit GÜLTEN; Selim NAK; Mahmut ÖZTÜRK; Ömer YERCİ (Turkish Journal of Gastroenterology, 2019)
-